KONTRIBUSI FIELD STUDY MAHASISWA PASCASARJANA DALAM PENGAJARAN DASAR-DASAR PENDIDIKAN ISLAM PADA PROGRAM MANAJEMEN PENDIDIKAN ISLAM UINSI SAMARINDA: PADA PROGRAM MANAJEMEN PENDIDIKAN ISLAM UINSI SAMARINDA - Anata Rifiyyah; Zamroni; Bahrani (STKIP Subang, 2025)
This study examines the contribution of postgraduate students participating in field study programs to the teaching of the Islamic Education Foundations course within the Islamic Education Management Program at UINSI Samarinda. As part of academic professional development, postgraduate students undertake a teaching practicum designed to strengthen pedagogical competence, classroom management skills, and instructional delivery aligned with the course learning objectives. This qualitative research employed a descriptive approach, using interviews, observation, and documentation to capture the real experiences of postgraduate students functioning as teaching assistants and temporary instructors. Findings reveal that the field study program provides three major contributions: enhancement of instructional practice, increased student engagement in learning, and improvement of teaching preparation and reflective professionalism. Students enrolled in the first semester demonstrated better understanding of key Islamic educational concepts when taught through interactive and student-centered approaches implemented by postgraduate mentors. The study also found that the presence of postgraduate student-teachers supports lecturers in managing large classes, diversifying materials, and integrating technology-based learning activities. Challenges identified include limited teaching time, adaptation to classroom dynamics, and the need for more structured mentoring. Overall, field study significantly contributes to the development of pedagogical capabilities among postgraduate students and enhances the quality of learning for undergraduate students. This research encourages the optimization of field study implementation in Islamic higher education institutions as a strategic step in preparing future lecturers.